Delineation of reduced CTV2 on the basis of the characteristics and distribution of cervical lymph node metastasis in nasopharyngeal carcinoma - Zhiqiang Wang; Yi Yang; Chunlei Ge; Rui Tian; Sheng Cheng; Jingyu Gao; Yan Wang; Qi Yue; Zhiwei Wang; Qingqing He; Yuchuan Xu; Yan Li; et al. (BMC Cancer)
Abstract Introduction The core objective of this study was to precisely locate metastatic lymph nodes, identify potential areas in nasopharyngeal carcinoma patients that may not require radiotherapy, and propose a hypothesis for reduced target volume radiotherapy on the basis of these findings. Ultimately, we reassessed the differences in dosimetry of organs at risk (OARs) between reduced target volume (reduced CTV2) radiotherapy and standard radiotherapy. Methods and materials A total of 209 patients participated in the study. We used image registration techniques to map patients’ neck metastatic lymph nodes onto a template CT of healthy individuals. Using MIM software, we integrated all patients’ lymph node images onto the template CT images and conducted an in-depth analysis of their distribution characteristics and metastatic patterns. Subsequently, we randomly selected the localization images of 30 patients and used paired t test methods to compare the differences in the dosimetry of target volumes and OARs between reduced target volume radiotherapy and standard radiotherapy. Results A total of 2314 metastatic lymph nodes were identified and mapped. There were no metastatic lymph nodes observed at level VIIb or within the lateral border of the common carotid artery. The percentages of metastatic lymph nodes at levels Ia, Ib, IIa, IIb, III, IVa, IVb, Va, Vb, Vc, VIa, VIb, VIIa, VIIb and VIII accounted for 0%, 1.5%, 22.8%, 41.1%, 15.9%, 3.0%, 0%, 4.4%, 1.0%, 0.3%, 0%, 0%, 9.7%, 0% and 0.3%, respectively, of the 2314 metastatic lymph nodes. Further analysis of the dosimetric outcomes revealed a significantly lower mean dose to the oral cavity, laryngeal cavity, esophagus, trachea, pharyngeal constrictor muscles, parotid gland, submandibular gland and thyroid gland with the implementation of reduced-target radiotherapy than with standard radiotherapy. Conclusion IMRT sparing level I, IVb, VI, and VIIb lymph nodes and the area within the lateral border of the common carotid artery for stage II-IVa NPC patients is feasible. This method can significantly reduce the dose to peripheral organs at risk.